PROFESSIONAL DEVELOPMENT IN FUNCTIONAL BASIC EDUCATION OF ADULTS - APPLICATION OF THE ACTION RESEARCH MODEL - Šarčević, Ivan (Metodička teorija i praksa, 2024)
The aim of this paper is to present the course and results of action research according to Stringer's model in a school for basic education of adults, where the opinions of employees about the experiences with the training attended and proposed steps to influence change or improvement in professional training were examined. The sample consisted of teachers and professional associates of the school (N=21), and the data was collected from several different sources (questionnaire, interview, training proposal for professional development). The results of this research confirmed the findings of earlier research on the inadequacy of training for the specific working conditions of certain types of schools, as well as the predominantly theoretical character of existing catalog training. Although the employees of the school created an action plan to improve their own professional development, not all elements of the plan could be evaluated in a short period of time. The main drawback of action research is the impossibility of drawing permanent and general conclusions. Therefore, additional research on the mentioned topic and the participation of a larger number of respondents are needed.
Keywords: functional basic education of adults; professional development; action research